Transition from shear to stress-assisted diffusion of copper–chromium nanolayered thin films at elevated temperatures. (November 2015) - Raghavan, R.; Wheeler, J.M.; Harzer, T.P.; Chawla, V.; Djaziri, S.; Thomas, K.; Philippi, B.; Kirchlechner, C.; Jaya, B.N.; Wehrs, J.; Michler, J.; Dehm, G.
Graphical abstract: Abstract: The mechanical behavior of Cu–Cr nanolayered films and an alloy film of nominal composition Cu20 Cr80 at.% was studied by microcompression testing at temperatures from 25 °C to 300 °C. Comparing nanolayered films, plastic deformation and failure occurred at consistently higher stress levels in the film with the smaller layer thicknesses. Plasticity in the nanolayered films always initiated in the softer Cu layers followed by a finite strain-hardening response in the stress–strain curves. Failure indicated by a strain-softening response following the higher peak strength due to shearing and tearing at columnar boundaries of Cr was observed in the nanolayered films at 25 °C and 100 °C. A transition from shearing and crack formation across the Cu–Cr interfaces leading to anomalous grain growth or beading of the nanocrystalline Cu layers was observed at elevated temperatures of 200 °C and 300 °C. On the other hand, the Cu20 Cr80 at.% alloy film exhibited failure by columnar buckling consistently at elevated temperatures, but shearing promoted by buckling at the highest strengths among the films at ambient temperature.